Sifat Mekanis Beton OPC Dan OPC POFA Menggunakan Air Gambut Sebagai Air Pencampur - Andrian Prasetyo; Monita Olivia; Ismeddyanto Ismeddyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water containing a low pH is not recommended as concrete mixing water. Water has a pH below 7 is acidic water. The acidity of peat water can damage the quality and service life of concrete in the long term. The addicid of the added material such as oil ash or Palm Oil Fuel Ash (POFA) may increase the formation of calcium silicate hydrate as a gel adhesive concrete. This study aims to measure the mechanical properties such as compressive strength, tensile strength and modulus elasticity of concrete with a compressive strength of 35 MPa. Concrete compressive strength OPC and OPC + 10% POFA using peat water as mixing water has decreased by 8.33% and 6.33% of the compressive strength of normal concrete. The results of tensile strength and modulus of elasticity sides show strong results in line with the press. The use of oil ash or Palm Oil Fuel Ash (POFA) showed a decrease in mechanical properties is smaller than OPC concrete with peat water as mixing water. The compressive strength of concrete using peat water as mixing water has a value of compressive strength greater than 90% of the compressive strength of normal concrete, so the peat water is still fit for use as concrete mixing water with treatment (curing) of plain water.Keywords: OPC, mechanical properties, palm oil fuel ash, peat water.